Scandalous knowledge : science, truth and the human - Smith, Barbara Herrnstein (Frontiers of theory., 2005)
This book explores the radical reconceptions of knowledge and science emerging from constructivist epistemology, social studies of science, and contemporary cognitive science. Smith reviews the key issues involved in the twentieth-century critiques of traditional views of human knowledge and scientific truth and gives an extensively informed explanation of the alternative accounts developed by Fleck, Kuhn, Foucault, Latour, and others. She also addresses the various anxieties (e.g., over 'relativism') and 'wars' occasioned by these developments, placing them in their historical contexts and arguing that they are largely misplaced or spurious. Smith then examines the currently perplexed relations between the natural and human sciences, the grandiose claims and dubious methods of evolutionary psychology, and the complex play of naturalist, humanist, and posthumanist ideologies in contemporary views of the relation between humans and animals.